Planting date, cultivar, seed treatment, and seeding rate effects on soybean growth and yield. Issue 1 (21st May 2020) - Nleya, Thandiwe; Schutte, Matthew; Clay, David; Reicks, Graig; Mueller, Nathan
Abstract: Soybean [ Glycine max (L.) Merr.] yield is a function of many factors including genetic attributes of the cultivar, environmental conditions, and management practices. Temporally variable weather patterns in North America, especially in the northern Great Plains, have resulted in the re‐examination of how spring production practices interact with the environmental conditions to influence yield. This study evaluated the impact of four plantings dates, four seeding rates, and two soybean maturity groups (MGs) using treated and untreated (control) seed on soybean growth, seed yield, and composition. The study was conducted at Volga, SD, in 2014, 2015, and 2016. The planting dates in the study ranged from early May to early July and the four seeding rates were 247, 000; 333, 500; 420, 000; 506, 500 seeds ha −1 . Stand establishment decreased as seeding rate increased irrespective of planting date. The number of growing degree days (GDDs) to R1 decreased with delayed planting. Delayed planting also decreased the number of GDDs to R8, the length of the reproductive phase (R1−R8), and seed yield. Delayed planting decreased seed yield for both MGs but the rate of decrease was greater for MG 2.4 than MG 1.4. Seed treatment increased seed yield irrespective of planting date. Seed protein was variable among planting dates and between MGs while seed oil decreased with delayed planting. The research documents the impact of delayed planting on soybean yield and quality and highlights the importance of early planting in soybean irrespective of maturity group and growth habit.